Decision Support System in the Selection of Community Facilitators in WISMP-2 Activities Using the Multi Factor Evaluation Process (MFEP) Method - Beni Andika; Rini Kustini; Elfitriani Elfitriani (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2018)
AbstractCommunity Assistance Personnel (TPM) act as facilitators, motivators and can help with problems that exist in water-using farmer associations, TPM is also expected to improve the ability of irrigation managers, water-use farmers and other irrigation beneficiaries in implementing irrigation management effectively, efficiently . Then a trained assistant is needed, has good skills and knowledge about irrigation and is responsible for carrying out the tasks. This will certainly complicate the BAPPEDA in determining the right choices according to the criteria they want. Decision Support System with MFEP method is the right method to solve the problem of selecting community assistants with many criteria such as candidate identity, understanding written tests, motivation / dedication and expectations. The Multi Factor Evaluation Process (MFEP) method of decision making is done by giving subjective and intuitive consideration to factors that are considered important. The resulting system provides an alternative choice in finding community assistants that match the desired criteria.